EFFECTIVENESS OF A SUPERFICIAL TREATMENT USING BIFENTHRIN TO PROTECT RADIATA PINE FRAMING FROM DAMAGE BY SUBTERRANEAN AND DRYWOOD TERMITES IN INDONESIA - Paimin Sukartana; Jim W. Creffield; Agus Ismanto; Neo E. Lelana; Rusti Rushelia (Indonesian Journal of Forestry Research, 2010)
Various experimental testing procedures were undertaken in Indonesia to determine the effectiveness of a patented superficial (envelope) treatment using bifenthrin to protect radiata pine framing material from damage by two species of subterranean termites (Macrotermes gilvus and Coptotermes curvignathus) and one species of drywood termite (Cryptotermes cynocephalus). Lengths of framing material (Pinus radiata sapwood) were commercially treated to the targeted retention of 0.02% m/m of bifenthrin in the outer 2 mm depth penetration zone of the material. The treated and untreated materials were subsequently cut into test specimens and exposed to M. gilvus in the field and a semi-laboratory trial, to C. curvignathus in the laboratory and a semi-laboratory trial and to C. cynocephalus in a laboratory trial. No supplementary treatment was performed on the exposed cut ends of the treated test specimens. The results from the trials clearly demonstrated that the superficial treatment of bifenthrin seemed effective in protecting test specimens of radiata pine framing material from significant damage by Indonesia’s most notorious termite species that often causes serious economic loss to the timbers. Termites were unable to damage any of the bifenthrin-treated surfaces of test specimens. Any obser ved damage by termites, albeit minor, was in all cases confined to the exposed cut ends of test specimens. In contrast, attack by termites on the untreated control test specimens caused damage of the samples ranging from light to heavy.